Uji Organoleptik dan Antioksidan Teh Daun Kelor dan Kulit Jeruk Purut Dengan Variasi Suhu Pengeringan - Ajeng, Rumantika Galuh; , Dra. Aminah Asngad, M.Si (2016)
Tea is the kind most widely consumed beverage , has efficacy for the body and enjoyed by brewing .Tea products isn't only produced from the tea leaves, but can be produced from the other leaves such as leaves of moringa oleifera. Moringa leaves contains tannin, steroids, triterpenoids, flavonoids, saponins, antarquino, and alkanoid where everything is an antioxidant. Rough-skinned lime peel contains essential oils to add aroma and citrus to the drink used as an antioxidant and anticancer. The purpose of this study to know the content of antioxidant and organoleptic qualities of Moringa leaf tea and rough-skinned lime with drying temperature variations. The study design with completely randomized design two factors, factor 1 Formulation of Moringa leaves:rough-skinned keffir lime 1: 1 (K1), 2: 1 (K2), 1: 2 (K3) and factor 2: Temperature Drying 45 ° C ( J1), 50 ° C (J2), and 55 ° C (J3). Research results show that the conclusion showed the highest antioxidant formulation of 2: 1 and a drying temperature of 45 ° C was 79.34% and the lowest antioxidant formulations of 1: 2 and a drying temperature of 50 ° C was 68.32%. Tea products were the most dominant color is brown , scent and taste of fresh , panelists received power is less fond of the Moringa leaf tea and rough-skinned lime